Guideline-Based Statin Eligibility, Coronary Artery Calcification, and Cardiovascular Events - Pursnani, Amit (JAMA, 2015)
IMPORTANCE: The 2013 American College of Cardiology/American Heart Association (ACC/AHA) guidelines for cholesterol management defined new eligibility criteria for statin therapy. However, it is unclear whether this approach improves identification of adults at higher risk of cardiovascular events. OBJECTIVE: To determine whether the ACC/AHA guidelines improve identification of individuals who develop incident cardiovascular disease (CVD) and/or have coronary artery calcification (CAC) compared with the National Cholesterol Education Program’s 2004 Updated Third Report of the Expert Panel on Detection, Evaluation, and Treatment of High Blood Cholesterol in Adults (ATP III) guidelines. DESIGN, SETTING, AND PARTICIPANTS: Longitudinal community-based cohort study, with participants for this investigation drawn from the offspring and third-generation cohorts of the Framingham Heart Study. Participants underwent multidetector computed tomography for CAC between 2002 and 2005 and were followed up for a median of 9.4 years for incident CVD. EXPOSURES: Statin eligibility was determined based on Framingham risk factors and low-density lipoprotein thresholds for ATP III, whereas the pooled cohort calculator was used for ACC/AHA. MAIN OUTCOMES AND MEASURES: The primary outcome was incident CVD (myocardial infarction, death due to coronary heart disease [CHD], or ischemic stroke). Secondary outcomes were CHD and CAC (as measured by the Agatston score). RESULTS: Among 2435 statin-naive participants (mean age, 51.3 [SD, 8.6] years; 56% female), 39% (941/2435) were statin eligible by ACC/AHA compared with 14% (348/2435) by ATP III (P < .001). There were 74 incident CVD events (40 nonfatal myocardial infarctions, 31 nonfatal ischemic strokes, and 3 fatal CHD events). Participants who were statin eligible by ACC/AHA had increased hazard ratios for incident CVD compared with those eligible by ATP III: 6.8 (95% CI, 3.8–11.9) vs 3.1 (95% CI, 1.9–5.0), respectively (P <.001). Similar results were seen for CVD in participants with intermediate Framingham Risk Scores and for CHD. Participants who were newly statin eligible (n = 593 [24%]) had an incident CVD rate of 5.7%, yielding a number needed to treat of 39 to 58. Participants with CAC were more likely to be statin eligible by ACC/AHA than by ATP III: CAC score >0 (n = 1015): 63% vs 23%; CAC score >100 (n = 376): 80% vs 32%; and CAC score >300 (n = 186): 85% vs 34% (all P < .001). A CAC score of 0 identified a low-risk group among ACC/AHA statin-eligible participants (306/941 [33%]) with a CVD rate of 1.6%. CONCLUSIONS AND RELEVANCE: In this community-based primary prevention cohort, the ACC/AHA guidelines for determining statin eligibility, compared with the ATP III, were associated with greater accuracy and efficiency in identifying increased risk of incident CVD and subclinical coronary artery disease, particularly in intermediate-risk participants.